Rights and privileges of accused person - Paul, Gopal Chandra (Dhaka : S.R. Paul, 2003)
With reference to Bangladesh.
Includes bibliographies.
Keywords: Due process of law -- Bangladesh; Criminal procedure -- Bangladesh